The Influence of Cigarette Advertising on Adolescent Smoking Behavior: Pengaruh Iklan Rokok Terhadap Perilaku Merokok Remaja - Yuliana Putri, Fauziah; Haryati, Omi; Nurhalimah, Nurhalimah; Dinarti, Dinarti (Essential English Grammar, 2024)
Adolescence is a transition period from childhood to adulthood. This period was the most turbulent and difficult. Because it often causes several problems, such as tobacco addiction. The proportion of smokers is higher in adolescents aged under 15 years than in adolescents aged over 15 years. The cause lies in teenagers' curiosity and desire to try something new. Gender, psychological factors, the influence of peers and parents, and tobacco advertising are some of the factors that cause teenagers to smoke. This research aims to determine the factors that influence smoking behavior among adolescents. This research uses a quantitative and a descriptive-analytical design using a cross-sectional approach. The research population was teenagers who had a smoking habit totaling 157 respondents. The sampling method used purposive sampling which was carried out at the research location of State Middle Schools (SMPN) in the East Jakarta area from June to October 2023. The samples in this study were by the criteria that had been set. determined to be 83 respondents. The results of this study show that there is a significant relationship between gender, peer influence, parental influence, and cigarette advertising on adolescent smoking behavior. Cigarette advertising is the most dominant factor influencing smoking behavior among teenagers, with OR = 4.458. This means that cigarette advertising is more likely to influence teenagers' smoking behavior. The government must limit tobacco advertising in electronic, newspaper, magazine,  and social media.